2018
DOI: 10.1111/apt.15059
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the risk of gastrointestinal bleeding in patients taking third‐generation P2Y12 inhibitors compared with clopidogrel

Abstract: Summary Background Ticagrelor and prasugrel are third‐generation oral P2Y12 receptor antagonists with rapid onset and pronounced platelet inhibition. However, higher overall bleeding rates have been reported for these agents when compared with clopidogrel. Aim To compare the risk of gastrointestinal bleeding (GIB) among users of third‐generation P2Y12 inhibitors with clopidogrel. Methods We systematically searched for published randomised controlled trials of ticagrelor or prasugrel versus clopidogrel until Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…Bleeding, as the most common side effects of thirdgeneration oral P2Y 12 inhibitors, has been well evaluated in previous studies [5][6][7]. Dyspnea was another important side effect, which was commonly reported in thirdgeneration oral P2Y 12 inhibitors users.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding, as the most common side effects of thirdgeneration oral P2Y 12 inhibitors, has been well evaluated in previous studies [5][6][7]. Dyspnea was another important side effect, which was commonly reported in thirdgeneration oral P2Y 12 inhibitors users.…”
Section: Introductionmentioning
confidence: 99%
“…Our results support the importance of gastrointestinal events because more than one in four patients treated with DAPT (29.5%) had at least one gastrointestinal event. The most common gastrointestinal event was anemia, which may have a negative effect on cardiovascular disease and has not been analyzed in previous reports [15].…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in the Study of platelet inhibition and patient outcomes (PLATO trial) [10], compared with the clopidogrel group, the ticagrelor group had a higher risk of major bleeding that was not related to coronary artery bypass graft. However, subsequent studies have yielded contradictory results, with an increased risk of bleeding with prasugrel and ticagrelor in some of them [9][10][11][12][13][14][15], but no differences between clopidogrel and these new compounds in others [16][17][18][19][20][21][22]. The main limitation of acquiring meaningful comparisons among studies and these antiplatelet agents is the variability in bleeding definitions used [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the bleeding risk assessment of each patient before using a P2Y 12 inhibitor was not mentioned. Since most previous published studies showed higher bleeding risk with ticagrelor or prasugrel, 2 this may have affected the clinical decision about P2Y 12 inhibitor selection following PCI. In fact, clopidogrel is the most common P2Y 12 inhibitor employed for acute coronary syndrome, especially in older patients and those at high risk of bleeding 5 .…”
mentioning
confidence: 99%